Production objectives, trait and breed preferences of farmers keeping N'Dama, Fulani Zebu and crossbred cattle and implications for breeding programs. (27th October 2016) - Traoré, S. A.; Markemann, A.; Reiber, C.; Piepho, H. P.; Valle Zárate, A.
Abstract : Many local livestock breeds in developing countries are being replaced by exotic breeds, leading to a loss of genetic resources. In southern Mali, for the past two decades, a trend towards increasing crossbreeding between the trypanotolerant N'Dama cattle and the trypano-susceptible Fulani Zebu cattle has been taking place. A survey with 160 farmers owning a cattle herd was carried out in southern Mali to investigate their production objectives, as well as trait and breed preferences and correlated socio-economic determinants in order to understand farmers' breeding decisions and to identify comparative advantages of three breed groups (N'Dama, Fulani Zebu and crossbreds) raised in the study area. Data were analyzed using an exploded logit model. The reasons for raising cattle, as well as trait and breed preferences reflected the multiple objectives of the farmers. Draught power and savings were the most important production objectives. Productive traits were ranked highest; farmers reported large body size as the most preferred trait, followed by fertility, draught ability and milk yield. Crossbreds were the favored breed group. Breed preferences were mainly explained by 'resistance to disease' for N'Dama cattle and 'high market price' for Fulani Zebu and crossbred cattle. Production objectives, trait and breed preferences were mainly influenced by farmer group (local farmers and settled transhumants). Local farmers put comparatively more emphasis on livestock functions linked to crop production such as draught power. They had a higher preference for traction ability as a selection trait and preferred N'Dama over Fulani Zebu cattle. Settled transhumants emphasized milk yield as a selection trait and preferred Fulani Zebu over N'Dama. The results indicate that the trend towards more crossbreeding will continue putting the N'Dama breed under high risk of genetic dilution in southern Mali. The N'Dama cattle remain a valuable breed due to their adaptive traits such as disease and drought tolerance and their good traction ability, fulfilling the diverse objectives of local farmers. Crossbreeding was found to be a promising breeding strategy, which might contribute to the maintenance of the local breed, provided that breeding schemes are thoroughly planned and organized.